Arginine-16 β2 adrenoceptor genotype predisposes to exacerbations in young asthmatics taking regular salmeterol. Issue 11 (13th June 2006) - Palmer, C N A; Lipworth, B J; Lee, S; Ismail, T; Macgregor, D F; Mukhopadhyay, S
Abstract : Background: The homozygous presence of the arginine-16 variant of the β2 adrenoceptor gene ADRB2 reverses the benefits from the regular use of short acting β2 agonists in asthmatic adults compared with the homozygous glycine-16 genotype. We studied the effect of this polymorphic variation on asthma exacerbations in children and young adults and its relation to long acting β2 agonists. Methods: A cross-sectional survey was undertaken using electronic records, direct interviews, and genotype determination of position 16 and 27 of the ADRB2 gene in DNA from mouthwash samples of 546 children and young asthmatics attending paediatric and young adult asthma clinics in Tayside, Scotland during 2004–5. The primary outcome measure was asthma exacerbations over the previous 6 months. Results: There was an increased hazard of asthma exacerbations across all treatment steps of the British Thoracic Society (BTS) asthma guidelines when the homozygous genotypes Arg/Arg and Gly/Gly were compared (OR 2.05, 95% CI 1.19 to 3.53, p = 0.010), particularly in patients treated with salmeterol (OR 3.40, 95% CI 1.19 to 9.40, p = 0.022). The Glu27Gln polymorphism had no significant effect on asthma exacerbations in any treatment group. Conclusions: The arginine-16 genotype of ADRB2 predisposes to exacerbations in asthmatic children and young adults, particularly in those exposed to regular salmeterol. This may be explained by genotype selective salmeterol induced downregulation and impaired receptor coupling, and associated subsensitivity of the response.